A Study on Maximum Skin Dose in Cerebral Embolization Procedures - D’Ercole, L.; Mantovani, L.; Thyrion, F. Zappoli; Bocchiola, M.; Azzaretti, A.; Di Maria, F.; Saluzzo, C. Massa; Quaretti, P.; Rodolico, G.; Scagnelli, P.; Andreucci, L. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: It is essential to measure the skin dose of radiation received by patients during interventional neuroradiologic procedures performed under fluoroscopic guidance, such as embolization of cerebral aneurysms, which is regarded as a high-dose interventional radiology procedure. In this study, we report a method for evaluating maximum skin dose (MSD), an ideal marker of radiation-induced effects, based on an innovative use of radiochromic films.MATERIALS AND METHODS: Forty-eight procedures were studied in 42 patients undergoing embolization of cerebral aneurysms. Fluoroscopic and digital dose-area product (DAP), fluoroscopy time, and total number of acquired images were recorded for all procedures. The MSD was measured using Gafchromic XR type R films.RESULTS: The MSD was measured in one group of 21 procedures. The coefficient (κ) of the interpolation line between the skin dose and the DAP (κ = 0.0029 cm−2) was determined. An approximate value of MSD from the DAP for the remaining 27 procedures was estimated by means of an interpolation line. The mean MSD was found to be 1.16 Gy (range, 0.23–3.20 Gy).CONCLUSION: The use of radiochromic XR type R films was shown to be an effective method for measuring MSD. These films have the advantage of supplying information on both the maximum dose and the distribution of the dose: this satisfies the most stringent interpretation of Food and Drug Administration, American College of Radiology, and international recommendations for recording skin dose.